PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI DIGITAL 23 SEMARANG - Harindra, Lazuardi Okva; Hidayat, Wahyu; Prihartini, Apriatni Endang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
Purchase decisions can provide maximum results if the product quality, service quality and price always considered. This research is done on Kedai Digital 23 Semarang. This type of research is explanatory research. Techniques of data collection using interviews, questionnaires and observation. The conclusion from this study is that there is influence between product quality, service quality and price on purchase decisions. Based on the conclusion that the company needs to pay attention to the quality of raw materials and the level of neatness product. Similarly, the performance of the employee so employees can provide the best service for customers by monitoring, provide guidance and conduct regular employee appraisal. As well as to continue to consider the price to be affordable to consumers.